A prospective cohort study on cognitive and psychological outcomes in COVID-19 ICU survivors at 3 months of follow up - Thomas, Merlin; Hameed, Mansoor; Hussein, Mousa; George, Saibu; Rajalekshmi, M. R.; Akram, Jaweria; Sharma, Rohit; Al Adab, Aisha Hussain O.; Ahmad, Mushtaq; Singh, Rajvir; Raza, Tasleem (Frontiers in Medicine, 2024)
The Outcomes -Short and Long term in ICU patient with COVID-19 "OUTSTRIP COVID-19" study was initiated to assess overall mortality, physical and psychiatric co-morbidities, reduction in lung function, and the ability to return to work post-ICU discharge with a follow-up period of 2 years in COVID-19 patients admitted to ICUs in Qatar. This paper focuses on the prevalence of cognitive impairment, depression, anxiety, and stress at baseline and 3 months after ICU discharge. Methods: This prospective cohort study included 100 ICU survivors reviewed at baseline within 7 weeks of ICU discharge, with a 3-month follow-up. Demographics, clinical characteristics, and relevant medical history were collected at baseline. Cognitive outcomes were assessed using the Montreal Cognitive Assessment-Basic (MoCA-B) tool, while psychological outcomes were evaluated using the Depression Anxiety and Stress Scale-21 (DASS-21).At baseline, 72% of ICU survivors exhibited mild cognitive impairment, which significantly improved to 56% at 3 months. However, severe cognitive impairment persisted in 20% of survivors at 3 months.For psychological outcomes, the mean depression score remained below 9 (5.64 ± 6.90) at both time points, with no significant change. At baseline, 25% of survivors had clinical depression, which reduced to 16% at 3 months.The mean anxiety score at baseline (9.35 ± 8.50) significantly decreased to 6.51 ± 7.74 (p = 0.002) at 3 months. Anxiety was not reported by 48% of survivors at baseline and this increased to 66% at 3 months. Severe to extremely severe anxiety decreased from 19% to 12% during the same period.The mean stress score at baseline (8.34 ± 8.07) did not significantly change at 3 months.At baseline, 18% experienced stress, which decreased to 12% at 3 months, with 5.3% facing severe to extremely severe stress.COVID-19 ICU survivors experience significant cognitive impairment, anxiety, and stress. While cognitive impairment and anxiety showed improvements at 3 months, depression and stress remained unchanged. These outcomes strongly emphasize the requirement for thorough post-ICU care and comprehensive mental health assistance for individuals recovering from COVID-19. Customized interventions and additional research endeavors are crucial to effectively manage the cognitive and psychological consequences faced by these patients.